Matrix data analysis methods for applications in laser beam position measurement modules - Budzyń, Grzegorz; Baranski, Jedrzej; Rzepka, Janusz (Photonics Letters of Poland, 2022)
This paper addresses the problem of selecting an optimal algorithm suitable for real-time processing of matrix sensor data in laser beam positioning applications. We compare four different algorithms and prove that the chosen one provides the same results in time by several orders of magnitude lower and with negligible memory consumption, making it suitable for use in microcontroller-based sensing modules. Full Text: PDF References S. Donati, Electro-Optical Instrumentation-Sensing and Measuring with Lasers (Prentice Hall, Upper Saddle River, NJ, 2004). DirectLink K.N. Joo, J.D. Ellis, E.S. Buice, J.W. Spronck, R.H. Munning Schmidt, "High resolution heterodyne interferometer without detectable periodic nonlinearity", Optics Expr. 18(2), 1159 (2010). CrossRef G. Budzyń, J. Rzepka, "Study on Noises Influencing the Accuracy of CNC Machine Straightness Measurements Methods Based on Beam Position Detection", J. Machine Engin. 20(3), 76 (2020). CrossRef Reference materials for PSD and CMOS sensors, , referenced 7-11-2022 CrossRef S. Das, A. Saha, "Laser Beam Position-Dependent PSD-Based Calibrated Self-Vibration Compensated Noncontact Vibration Measurement System", IEEE Trans. Instr. Meas. 68(9), 3308 (2019). CrossRef P. Zhang, J. Liu, H. Yang, L. Yu, "Position Measurement of Laser Center by Using 2-D PSD and Fixed-Axis Rotating Device", IEEE Access 7, 140319 (2019). CrossRef J. Rzepka, G. Budzyn, "Laser measurement system for machine tools", Proc. SPIE 5144, 840 (2003). CrossRef S. Xiang, H. Li, M. Deng et al., "Geometric error identification and compensation for non-orthogonal five-axis machine tools", Int. J. Adv. Manuf. Technol. 96, 2915 (2018). CrossRef N. Hagen, E. Dereniak, "Gaussian profile estimation in two dimensions", App. Opt. 47(36), 6842 (2008). CrossRef S.M. Ross, Introduction to Probability and Statistics for Engineers and Scientists (Academic Press 2014). CrossRef